Ichnology of the carbonate aeolianites of the Quaternary Gargaresh Formation, western Libyan coast. (مجلة البحوث الأكاديمية, 2018)
Quaternary carbonate aeolianites are well exposed in sea cliffs along the western coast of Libya. These deposits form the major part of the Gargaresh Formation; also include paleosols and shallow marine facies. The aeolianites and paleosols contain abundant calcified root structures; rhizolithes. The presence of abundant rhizoliths at several horizons of the aeolianites indicates that the carbonate dunes were stabilized at least episodically by vegetation during relatively wet period. Animal trace fossils recorded in the aeolianites include several specimens of Skolithos linearis burrows; vertical or nearly vertical to bedding planes. Also irregularly meandering burrows parallel to stratification have been recorded in the aeolianites.